Origami Microwave Imaging Array: Metasurface Tiles on a Shape‐Morphing Surface for Reconfigurable Computational Imaging (Adv. Sci. 28/2022). Issue 28 (5th October 2022) - Venkatesh, Suresh; Sturm, Daniel; Lu, Xuyang; Lang, Robert J.; Sengupta, Kaushik
Abstract : Origami Microwave Imaging Arrays Shape morphing architectures when combined with antenna/radiating elements lead to dynamically reconfigurable platforms which could potentially enable joint communication‐sensing radio frequency (RF) applications. In article number 2105016, Suresh Venkatesh and co‐workers combine origami approaches along with broadband metasurfaces to demonstrate a scene adaptive microwave computational imaging system. Such electromagnetic‐origami RF cameras open new avenues in intelligent and robust sensing and imaging systems.